The relationship between self-esteem and intimate partner violence (IPV): The mediating role of resilience - Chaddher, Samina Ashraf; Ahmad, Roselisa Binti (International Journal of Psychosocial Rehabilitation, 2020)
Intimate partner violence (IPV) is an emerging issue in social science literature. Most of the studies on IPV has focused on the its after effects. However, there is lack of research that explore the factors for reducing the adverse psychological effects of such violence. Therefore, the present study aims to assess the impact of self-esteem on IPV through resilience. In order to meet the objective of the study, the data was collected from 309 bettered working women in Pakistani colleges through self-administered questionnaires. The data was analyzed by applying PLS-SEM approach using SmartPLS 3.2.8. The findings of the study explained a positive association between both dimensions of self-esteem (i.e. self-competence and self-liking) with resilience and negative association between resilience and IPV. The study also inferred full mediation of resilience between the relationship of self-competence and self-liking with IPV. The study also explains the research implications, limitation and future directions in the last section.